Kolaborasi Ekonomi, Hukum dan Musik: Strategi PkM untuk Penguatan Komunitas Kreatif di Gereja SIB Tanjung Malim Malaysia - Nopeline, Nancy; Lumban Gaol, Manatap Berliana; Debora, Debora; Batubara, Junita; Wong, Colleen (Indra Institute Research & Publication, 2025)
This Community Service (PkM) is one of the important pillars in community development and empowerment efforts. Collaboration of Economy, Law, and Music: CSP Strategy for Strengthening Creative Communities at SIB Church Tanjung Malim Malaysia aims to improve the capacity and skills of the church community through an interdisciplinary approach. This service integrates aspects of economy, law, and music arts to create a comprehensive and sustainable program in empowering creative communities. Through a series of trainings, this service seeks to increase community understanding of the socialization of digital financial literacy and financial processing to improve self-competence, personal data protection of consumers as users of online loan services. In addition, this activity also includes music training and choir resonance by finding the power of collective voices that aim to develop the musical talents and skills of community members. Collaboration between economists, legal experts, and professional musicians is at the heart of this approach, creating a strong synergy for community empowerment. The results of this CSP show a significant increase in participants' knowledge and skills in the fields of creative economy, legal awareness, and musical ability. Participants also showed a high interest in applying the knowledge gained to develop their own creative businesses. The program evaluation shows that the integration of these three aspects has successfully created a holistic positive impact, strengthening the creative community at the SIB Church in Tanjung Malim. This PkM highlights the importance of a collaborative and interdisciplinary approach to achieve maximum and sustainable results. This experience can be a model for similar initiatives in other communities, encouraging the development of a creative economy based on legal understanding and musical skill enhancement.